Total Economic Valuation of Coral Reef Ecosystems and Ecotourism Carrying Capacity for Sustainable Management of the Gita Nada Marine Protected Area, West Lombok - Syarif Husni; Sitti Hilyana; L. Sukardi; Muhammad Junaidi (Postgraduate, University of Mataram, 2026)
Economic valuation alone is insufficient if it is not complemented by an analysis of environmental carrying capacity, particularly in areas designated for ecotourism development. This study aims to estimate the total economic value (TEV) of coral reef ecosystems and to assess the ecotourism carrying capacity within the Gita Nada Marine Protected Area (MPA) in West Lombok Regency. A descriptive research approach was employed using survey techniques involving three respondent groups: ecosystem service users (fishermen, n = 24), tourists (n = 40), and stakeholders (n = 11), totaling 75 respondents. Direct and indirect use values were estimated using market price, surrogate market, and replacement cost methods, while non-use values were derived through willingness-to-pay (WTP) surveys and benefit transfer. The findings indicate that the total economic value of coral reefs in the Gita Nada MPA reaches IDR 74,961,205,060.00 per year, with the largest component being existence value (IDR 28,782,000,000.00 per year). The ecotourism carrying capacity based on Government Regulation No. 18 of 1994 (10% of utilization zone) is estimated at 275 visitors per day for diving and 137 visitors per day for snorkeling, and 137 visitors per day for beach-based recreation. These values underscore the importance of sustainable conservation management to preserve the long-term ecological and economic benefits of the Gita Nada MPA.